Incidence and correlates of opioid-related psychiatric emergency care: A retrospective, multiyear cohort study - Bahji, MD, Anees (Journal of Opioid Management, 2020)
Background: In 2018, nearly 4,000 Canadian lives were claimed by the opioid epidemic. To date, only a few studies have reviewed shifts in emergency department (ED) utilization for opioid-related psychiatric presentations. Aims: To describe the characteristics of patients seeking ED care for opioid-related psychiatric presentations and to identify demographic and clinical characteristics that were associated with psychiatric inpatient admission for such presentations. Methods: Retrospective cohort study with multivariate logistic regression. Findings: Over a 4-year period, 555 opioid-related presentations were recorded (50 percent female, mean age 40.0 years). Time trend analysis showed a nonsignificant increase in the number of visits by fiscal year. The most common reason for ED presentation relevant to opioids was opioid withdrawal (49 percent). Nearly 20 percent of all visits required psychiatric admission; predictors of psychiatric admission were arrival by ambulance (adjusted odds ratio (AOR) = 2.03), older age (AOR = 1.05), longer length of ED stay (AOR = 1.10), and more severe triage score (AOR = 0.4). Sex and referring service were not associated with disposition in the ED. Admissions were more likely for opioid intoxication and withdrawal. Conclusion: EDs are serving increasing numbers of patients in psychiatric crisis related to opioid-use. A decision support tool could be developed and validated in the future to provide reliable, clinically relevant information to providers and case managers relevant to opioid-related ED presentations.